Hubungan antara Beban Kerja, Konflik Peran, dan Dukungan Sosial dengan Stres Kerja Pada Guru di Sekolah Menengah Atas Negeri 1 Manado Pada Masa Pandemi Covid-19 - Merdekawati Evangli Weken; Arthur Elia Mongan; John Socrates Kekenusa (Indonesian Journal of Public Health and Community Medicine, 2020)
Background: A survey conducted by the Yale Center for Emotional Intelligence and Collaborative for Social Emotional and Academic Learning in 2020 among more than 5000 teachers in the United States showed that teachers experienced work stress in carrying out learning activities and working from home during this pandemic. Various countries in the world, including Indonesia, have taken policies by presenting alternative education processes online and it is very influential not only for students but also for teachers. UNESCO (2020) states that around 63 million teachers around the world must be faced with an educational process that is very different from before this can be done by school closures in around 165 countries and this can trigger work stress on teachers. This study aims to analyze the relationship between workload, role conflict, and social support with work stress among teachers at SMA N 1 Manado during the Covid-19 pandemic. Method: This research was a quantitative analytic survey research using a cross sectional design. The research sample was 76 teachers who were willing to be respondents. The instrument used was the NIOSH Job Stress Questionnaire (1999) in the form of googleform. Univariate analysis was conducted to see the response of each variable under study, the bivariate analysis used the chi-square test to see the relationship between 2 variables and multivariate analysis used logistic regression to see which variables had the most influence on work stress. Results: The results showed that there was a relationship between workload and work stress (p = 0,000), there was a relationship between role conflict and social support (p = 0,000), there was a relationship between social support and workload (p = 0,002). The results of the multivariate test showed that social support (p = 0,007; OR = 25,402) was the most influential variable with work stress on teachers at SMA N 1 Manado. Conclusion: It can be concluded that there is a significant relationship between workload, role conflict, and social support with work stress among teachers at SMA N 1 Manado. The variable that most influences work stress is social support.